2011
DOI: 10.1523/jneurosci.2369-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cocaine Induces Fast Activation of D1 Receptor and Progressive Deactivation of D2 Receptor Striatal Neurons:In VivoOptical Microprobe [Ca2+]iImaging

Abstract: Cocaine induces fast dopamine increases in brain striatal regions, which are recognized to underlie its rewarding effects. Both dopamine D1 and D2 receptors are involved in cocaine’s reward but the dynamic downstream consequences of cocaine effects in striatum are not fully understood. Here we used transgenic mice expressing EGFP under the control of either the D1 receptor (D1R) or the D2 receptor (D2R) gene and microprobe optical imaging to assess the dynamic changes in intracellular calcium ([Ca2+]i) respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 49 publications
(53 reference statements)
4
61
0
Order By: Relevance
“…Moreover, the combined treatment of D1R and D2R antagonists produced less locomotor activity than D1R and D2R antagonists alone. In terms of mediation of reward induced by cocaine, the stimulation of D1R results in fast neuronal activation, and the stimulation of D2R results in progressive neuronal deactivation [7]. The weaker behavioral sensitization by cocaine was developed in the D1R-and D2R-KO mice compared to the WT mice, although repeated cocaine administration still induced behavioral sensitization in both D1R-and D2R-KO mice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the combined treatment of D1R and D2R antagonists produced less locomotor activity than D1R and D2R antagonists alone. In terms of mediation of reward induced by cocaine, the stimulation of D1R results in fast neuronal activation, and the stimulation of D2R results in progressive neuronal deactivation [7]. The weaker behavioral sensitization by cocaine was developed in the D1R-and D2R-KO mice compared to the WT mice, although repeated cocaine administration still induced behavioral sensitization in both D1R-and D2R-KO mice.…”
Section: Discussionmentioning
confidence: 97%
“…The striatonigral pathway (direct pathway) contains neurons with dynorphin, substance P, and dopaminergic D1 receptors (D1R), whereas striatopallidal pathway (indirect pathway) preferentially contains neurons with enkephalin and dopamine D2 receptors (D2R) [6]. D1R and D2R antagonists inhibited locomotor activity induced by psychostimulants [7,8]. However, the concomitant administration of D1R and D2R agonists enhances behavioral sensitization (BS) [9].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy is likely to reflect methodological differences; specifically, we measured the attenuation of D 1 R by cocaine (monitoring changes in intracellular Ca 2ϩ ) as opposed to electrophysiological responses of D 1 R-exressing neurons to high-frequency stimulation. Also, sensitization responses were measured several days after the last cocaine administration and are associated with changes in synaptic expression of AMPA receptors in MSNs (Boudreau et al, 2007;Kourrich et al, 2007), whereas our measurements were performed while mice were on cocaine and 24 h after the prior cocaine dose. On the other hand, our findings are consistent with those from a study that reported reduced membrane excitability of D 1 R-expressing MSNs in a brain slice preparation in the nucleus accumbens in mice previously exposed to repeated cocaine injections (5 days), though the membrane excitability of D 2 R-expressing MSNs was not affected (Kim et al, 2011) when compared with drug-naive mice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, sensitization responses were measured several days after the last cocaine administration and are associated with changes in synaptic expression of AMPA receptors in MSNs (Boudreau et al, 2007;Kourrich et al, 2007), whereas our measurements were performed while mice were on cocaine and 24 h after the prior cocaine dose. On the other hand, our findings are consistent with those from a study that reported reduced membrane excitability of D 1 R-expressing MSNs in a brain slice preparation in the nucleus accumbens in mice previously exposed to repeated cocaine injections (5 days), though the membrane excitability of D 2 R-expressing MSNs was not affected (Kim et al, 2011) when compared with drug-naive mice. Also, in nonhuman primates repeated cocaine exposure was associated with reductions in D 1 R levels in striatum (Moore et al, 1998), though human studies failed to observe this (Martinez et al, 2009), and thus it is unclear whether chronic cocaine exposure reduces the levels of D 1 R in striatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation